Synthesis, characterization, and evaluation of antimicrobial performance of N-[3-(dimethylamino)propyl]methacrylamide based copolymer on pathogens - Pihtili, Guzin; Sonmez, Pinar Erecevit; Biryan, Fatih; Torgut, Gulben (Wiley, 2022)
In this study, poly{N-[3-(dimethylamino) propylmethacrylamide-co-acrylonitrile}; [P(DMAPMA-co-AcN)] copolymer was polymerized by free radical polymerization (FRP) in the presence of azobisisobutyronitrile (AIBN) initiator at 60 degrees C. The structure of the synthesized polymer was characterized by the Fourier transform infrared (FT-IR), differential scanning calorimetry (DSC), and thermogravimetric analysis (TGA) methods. The bactericidal and fungicidal effects of the solutions prepared by adding methanol to this copolymer to prevent the growth of pathogenic bacteria, yeast, and fungi were evaluated by disk diffusion and broth microdilution method. Since the resistance of bacteria, yeast and fungi, which adversely affect human health, to antibiotics is an important issue, and there has not been any study on the antimicrobial properties of this copolymer, it has directed us to investigate its antimicrobial properties. According to antimicrobial susceptibility tests: The polymer solution showed a broad spectrum of antimicrobial action with 12.3-14.3 mm/inhibition zone diameter on Pseudomonas aeruginosa, Klepsiella pneumoniae, Enterococcus faecalis bacteria, Candida tropicalis, Epidermophyton floccosum yeast and fungi and showed a narrow spectrum of effect on inhibition of the growth of Candida albicans with 10.3 mm/inhibition zone diameter. No antimicrobial effects were observed on Staphylococcus aureus. The minimum inhibition concentration (MIC) value on the test microorganisms was determined as 125-31.25 mu l. The data obtained prove that the polymer is in the same group as the interaction of bactericidal and fungicidal drugs. It is also important as a polymer with antimicrobial properties. This study aimed to produce a new polymer with antimicrobial properties. This polymer can be a new and yielding antimicrobial representative in different areas.
Keywords: antimicrobial performance; copolymer; methacrylamide monomer; pathogens